2019
DOI: 10.21203/rs.2.10937/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Moving beyond individual barriers and identifying multi-level strategies to reduce anemia in Odisha India

Abstract: Background: To reduce the prevalence of anemia, the Indian government recommends daily iron and folic acid supplements (iron supplements) for pregnant women and weekly iron supplements for adolescents and all women of reproductive age. The government has distributed free iron supplements to adolescents and pregnant women for over four decades. However, initial uptake and adherence remain inadequate and non-pregnant women of reproductive age are largely ignored. The aim of this study is to examine the multileve… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…We included a narrow age-range of adolescents in our analysis because of the data constraints. It is suggested that early (10 to 14) and late (15)(16)(17)(18)(19) adolescence differ in health status and its determinants. It is possible that younger adolescents (10 to 14 years), who likely have less autonomy than the older adolescents, could be more affected by several aspects related to norms of care, feeding practices, and other health behaviors, in the family; which in turn are arguably affected by the broader socio-cultural norms and behaviors of the educated women in the community.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We included a narrow age-range of adolescents in our analysis because of the data constraints. It is suggested that early (10 to 14) and late (15)(16)(17)(18)(19) adolescence differ in health status and its determinants. It is possible that younger adolescents (10 to 14 years), who likely have less autonomy than the older adolescents, could be more affected by several aspects related to norms of care, feeding practices, and other health behaviors, in the family; which in turn are arguably affected by the broader socio-cultural norms and behaviors of the educated women in the community.…”
Section: Discussionmentioning
confidence: 99%
“…reproductive age, as important beyond individual-level factor, resulting in poor uptake of iron supplementation. Although the focus of their qualitative inquiry was on exploring barriers to iron supplementation in women,15 they have identified the need for addressing social norms, as extra-individual level factors in reducing anemia burden in India. itself is a bar set too low.…”
mentioning
confidence: 99%
“…The sample description is published elsewhere. 11 The final sample for the perceptual mapping and card sorting exercise comprised women of reproductive age (n=30), mothers-in-law (n=30) and men (n=30). All participants were required to live in the Angul District, speak Odiya, and give written consent before participating.…”
Section: Methodsmentioning
confidence: 99%
“…A more detailed description of the focus group discussion procedures can be found in a separate study. 11 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation